The Competences of Kurdistan Region Employees Disciplinary Committee and appealing its provisions. - امىدرس امدكخِر وُدي خىدي وُدي; امىدرشث امىصاغدة ٌَد غتداألوير غنِش (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
Employees Discipline Commission of the Iraqi Kurdistan region has two Jurisdictions. First, looking to appeals of employees’ civil services rights and its provisions are subjected to cassation appeal. Second, looking to the appeals of punishments issued under the Employees Discipline Law and its provisions is definite which is unjustified. so we proposed that all Commission’s provisions be subject to cassation appeal regardless the matter of the judgment especially as some of the punishments, has a greater impact than certain service rights. We are in intention for strengthening employee’s guarantees to achieve the balancing between the effectiveness of management and employee’s guarantees. This research included suggestion to establish a high administrative court in the Kurdistan Region to undertake the jurisdictions of the General Assembly of the Region’s Shura Council as attributive cassation. Also the jurisdiction of appointing competent authority for appeared conflicts on jurisdiction between the Administrative Court and the Employees Discipline Commission. Additionally, to give jurisdiction to the Appointment competent authority Commission to look on jurisdiction’s conflict between Employees Discipline Commission and Civil Courts. As for the (15) days period of the cassation appeal is insufficient to study the judgment and then resort to appeal it or not.